Pendekatan Model ADDIE dan Framework MDA pada Gamifikasi Edukasi Pendidikan Seks Anak Usia Dini - Hayat, Cynthia; Cancerita, Stefani (Fakultas Ilmu Komputer, Universitas Brawijaya, 2022)
Tujuan dari penelitian ini adalah melakukan edukasi mengenai pendidikan seks pada anak pada usia dini sesuai dengan kategori umur yang ditentukan oleh WHO. Pendekatan gamifikasi digunakan dalam penyampaian informasi dikarenakan menunjukkan grafik positif dalam memotivasi meningkatkan lingkungan belajar yang positif. Kontribusi penelitian ini dengan mengembangangkan aplikasi gamifikasi untuk edukasi pendidikan seks dilakukan dengan menggunakan model ADDIE dikombinasikan dengan pendekatan elemen-elemen pada framework MDA (Mechanics, Dynamics and Aesthetics). Tahapan-tahapannya dimulai dengan praproses potensi masalah, analysis, design, development, implementation, dan evaluation yang akhirnya akan menjadi final model setelah dilakukan uji respon pengguna terhadap aplikasi yang dikembangkan. Sedangkan fokus elemen pada framework MDA yang digunakan diantaranya elemen mechanics meliputi; genre,goal, platform, rating, level, dan concept art, elemen dynamic meliputi; storyline, game controls, challenge, dan game rules, sedangkan elemen aesthetics meliputi; sensation, narrative, dan submission. Aplikasi game ini juga telah diujicobakan ke 45 user dengan hasil dari uji respon pengguna dari pengguna game dengan hasil persentase 89% (Sangat Baik). AbstractThe aim of this study is to educate children about sex education at an early age according to the age category determined by WHO. The gamification approach is used in delivering information because it shows a positive graphic in motivating to improve a positive learning environment. The contribution of this study by developing gamification applications for sex education education is carried out using the ADDIE model combined with the approach to elements of the MDA framework (Mechanics, Dynamics and Aesthetics). The stages begin with a preprocessing of potential problems, analysis, design, development, implementation, and evaluation which will eventually become the final model after testing the user response to the developed application. While the focus elements on the MDA framework used include mechanics elements including; genre, goal, platform, rating, level, and concept art, dynamic elements include; storyline, game controls, challenges, and game rules, while aesthetics elements include; sensation, narrative, and submission. User responses are carried out to find out that the application of gamification of sex education education in early childhood is empirically tested and measured at all stages of development in the ADDIE and MDA models. This game application has also been tested on 45 users by using the ideal score (criteria) which is used to calculate the rating scale or interval score and the total number of answers. The percentage result is 89% (Very Good).